BUILDING RELIGIOUS MODERATION IN THE MILLENNIAL GENERATION: CHARACTER EDUCATION AS THE FOUNDATION FOR WISDOM AND MORAL LEADERSHIP - Arif Muzayin Shofwan (INTERNATIONAL JOURNAL OF SOCIETY REVIEWS, 2025)
This study examines the crucial role of character education in fostering religious moderation among the millennial generation, particularly in the context of increasingly polarized religious discourse. Using a qualitative descriptive methodology with a library research approach, this research investigates how character education can serve as a foundation for developing wisdom and moral leadership among millennials. The findings reveal that character education that emphasizes critical thinking, empathy, cultural awareness, and ethical reasoning significantly contributes to religious moderation. Furthermore, this study identifies specific pedagogical approaches that effectively promote moderate religious attitudes while respecting diverse belief systems. Educational institutions, religious organizations, and policymakers can utilize these insights to design programs that cultivate religious moderation and prepare millennials for moral leadership roles in pluralistic societies. This research contributes to the growing body of literature on religious education reform, character development, and the promotion of peaceful coexistence in diverse religious landscapes.